The Influence of Selection, Placement and Development on Employee Performance at Company X - Afifah, Zahra; Kustini, Kustini; Sugito, Sugito (Kontigensi : Jurnal Ilmiah Manajemen, 2025)
The main problem in this study is the less than optimal employee performance in company X. This study aims to determine the influence of selection, placement and development on employee performance. The method used is SEM PLS with a sample of 88 employees using saturated sampling techniques. Data were collected by distributing questionnaires to 88 respondents. The results showed that selection had no effect on employee performance. While for the influence of placement and development, there was a positive and significant influence on employee performance in company x.